2005
DOI: 10.1007/s00421-005-1374-8
|View full text |Cite
|
Sign up to set email alerts
|

Body composition is related to increase in plasma adiponectin levels rather than training in young obese men

Abstract: We assessed the major factors regulating adiponectin levels and the influence of exercise training on adiponectin levels in young obese men (19.2 +/- 1.1 yrs, BMI: 31.1 +/- 4.2, %fat: 27.2 +/- 3.9%). Subjects were separated into three groups (aerobic exercise group [AE: n=7], aerobic and resistance exercise group [AE + RE: n = 7], control group [n = 7]). AE underwent an 8-week training program (three times per week, more than 30 min endurance exercise at ventilatory threshold (VT) intensity). AE + RE went thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
157
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(167 citation statements)
references
References 48 publications
4
157
0
6
Order By: Relevance
“…Although it is not clear whether long-standing low adiponectin levels from an early age has an adverse effect, it appears of great importance to elucidate the mechanisms underlying the low adiponectin levels not only in middle-aged subjects but also in young subjects to prevent lifestyle-related diseases. A few studies have been conducted on the relationship between adiponectin levels and aerobic exercise training [10,11], and it was reported that the exercise training was not able to increase adiponectin levels in obese young men [13,33]. However, the effect of aerobic exercise on adiponectin levels in obese young women is not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is not clear whether long-standing low adiponectin levels from an early age has an adverse effect, it appears of great importance to elucidate the mechanisms underlying the low adiponectin levels not only in middle-aged subjects but also in young subjects to prevent lifestyle-related diseases. A few studies have been conducted on the relationship between adiponectin levels and aerobic exercise training [10,11], and it was reported that the exercise training was not able to increase adiponectin levels in obese young men [13,33]. However, the effect of aerobic exercise on adiponectin levels in obese young women is not known.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that basal adiponectin concentration was not altered after longterm exercise [10][11][12][13][14]. In contrast, Kriketos et al [15] recently reported that fasting adiponectin levels increased by 260% above baseline values after 2-3 bouts of low to moderate intensity exercise.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that modifications in body weight or body composition might be responsible for alterations in adiponectin levels (Esposito et al 2003;Hulver et al 2002;Monzillo et al 2003). Recent reports indicate that in young obese men, adiponectin levels are increased following an improvement of the body composition and this is more important than the way training is performed (Hara et al 2005). The present study examined the acute effects of exercise where there was no evidence of body weight change and this could explain the lack of modifications in adiponectin levels.…”
Section: Discussionmentioning
confidence: 99%